Educación popular Crisis y perspectivas - GADOTTI, Moacir comp. (MIÑO Y DAVILA, 1993)
Contiene colaboradores: WANDERLEY, Luiz Eduardo; PUIGGROS, Adriana; RODRIGUEZ BRANDAO, Carlos; FREIRE, Paulo; SIRVENT, María Teresa; GADOTTI, Moacir; HERNANDEZ, Isabel; FISCHMAN, Gustavo